Pharmacokinetic and Drug Absorption Profiles of the Anti-Hyperglycaemic Agent Gliclazide in Oral Tissue-Targeted Microcapsules in Rats - Jovic, Jelena; Milijasevic, Boris; Vukmirovic, Sasa; Vasovic, Velibor; Mikov, Momir; Mooranian, Armin; Al-Salami, Hani; Golocorbin-Kon, Svetlana (Masaryk University, 2020)
Background/Aim: Gliclazide is one of the most commonly prescribed oral anti-hyperglycaemic therapies in type 2 diabetes mellitus (T2D). Recently reported additional beneficial pharmacological properties of gliclazide, including immunomodulatory and anticoagulant activities, suggested its potential application in treatment of type 1 diabetes mellitus (T1D). However, following oral administration, gliclazide was shown to have poor and variable absorption directing research into development of novel pharmaceutical delivery systems of gliclazide suitable for T1D. Since bile acids have previously demonstrated stabilising and controlled-release effects on microcapsules, their use for preparation of microcapsules of gliclazide may lead to improvements in gliclazide release, absorption and antidiabetic effects. This investigation was aimed to evaluate drug absorption profiles and hypoglycaemic effects of alginate-based microcapsules of gliclazide, prepared together with or without cholic acid, in healthy rats. Methods: Thirty healthy Wistar rats with confirmed normal glucose blood concentration were allocated into five groups and administered with a single dose of either vehicle microcapsules, gliclazide in suspension, gliclazide microcapsules, gliclazide in suspension together with cholic acid or microencapsulated gliclazide in combination with cholic acid. Following respective gliclazide dose, blood was sampled over next 10 hours and blood glucose levels and gliclazide serum concentrations were measured. Results: This analysis demonstrated altered effects of different gliclazide formulations in healthy rats with the highest gliclazide absorption mirrored by the most profound hypoglycaemic effect being achieved after its oral administration as a suspension (p <0.01) compared to any other investigated pharmaceutical formulation. Conclusion: When conducting pharmacokinetic characterisation of novel pharmaceutical formulations of antidiabetic drugs, it is of utmost importance to select the appropriate research model and consider the possible role of gut-metabolic activation on their hypoglycaemic effects.